The Thermosphere Is a Drag: The 2022 Starlink Incident and the Threat of Geomagnetic Storms to Low Earth Orbit Space Operations - T. E. Berger; M. Dominique; G. Lucas; M. Pilinski; V. Ray; R. Sewell; E. K. Sutton; J. P. Thayer; E. Thiemann (Space Weather)
Abstract On 03 February 2022, SpaceX launched 49 Starlink satellites, 38 of which re‐entered the atmosphere on or about 07 February 2022 due to unexpectedly high atmospheric drag. We use empirical model (NRLMSIS, JB08, and HASDM) outputs as well as solar extreme ultraviolet occultation and high‐fidelity accelerometer data to show that thermospheric density was at least 20%–30% higher at 210 km relative to the 9 days prior to the launch due to consecutive geomagnetic storms related to solar eruptions from NOAA AR12936 on 29 January 2022. We model the orbital altitude and in‐track position of a Starlink‐like satellite in a low‐drag configuration at 200 km during minor (G1) and extreme (G5) geomagnetic storms to show that an extreme storm would have at least a factor of two higher impact, with cumulative in‐track errors on the order of 10,000 km after a 5‐day duration extreme storm. Comparison of the JB08 and NRL MSIS models relative to the HASDM model during modeled historical minor and extreme geomagnetic storms shows that in‐track errors on the order of 100 km per day at 250 km, decreasing to cumulative errors on the order of 1 km per day at 550 km during geomagnetic storms. We conclude that full‐physics, data assimilative, coupled models of the magnetosphere and upper atmosphere, as well as new operational satellite missions providing “nowcasting” data to launch controllers, space traffic coordinators, and satellite operators, are needed to prevent similar—or worse—orbital system impacts during future geomagnetic storms.